Multidimensional child poverty and its determinants: Empirical evidence from Sub-Saharan Africa - Waheed Mobolaji Ashagidigbi; Abiodun Daniel Akinyeke; Kehinde Oluseyi Olagunju; Abiodun Olusola Omotayo; Sheu Adekunle Salau; Joseph Omotoso Ajayi; Olanrewaju Micheal Akinsete (Economy, Business and Development: An International Journal (EB&D), 2024)
Poverty has been a subject of global discourse most especially in sub-Saharan Africa, where little progress has been achieved. Most literature sources regard poverty mainly as a household threat rather than one to affects the children living within the household. Thus, through a multidimensional approach, this study analyses poverty, specifically in the context of its effect on children. In carrying out this study, the General Household Survey data for Nigeria (the most populous country in sub-Saharan Africa) for 2018/2019 obtained from the National Bureau of Statistics (NBS) was used. Descriptive statistics, the Multidimensional Poverty Measure, and the Tobit Regression Model were employed in this study. The results showed that there are more male children (52.17%) than females (47.83%), with most of the children falling within the middle-age group (45.51%). Less than half of the household heads were found to be literate, while the mean size of the household amounted to nine. This study found that the poverty dimension mainly affecting the research sample of Nigerian children was their deprivation in terms of sanitation, while the least significant dimension was their lack of food. Child poverty is prevalent among the three respective age groups of children, among rural dwellers (57.16%), and among residents in the northern divide of the country.~ The rural sector, the residents in the northeastern region of the country, and the gender of the household head were found to be significant variables influencing child poverty in Nigeria. As such, poverty reduction strategies directed towards the rural sector, the northern region, and the identified age groups of children should be of primary focus in tackling child poverty in Nigeria to achieve the United Nations' Sustainable Development Goal (SDG1) - "End poverty in all its forms everywhere".
Keywords: 330; Child age categories; Child deprivation; Multidimensional Poverty Measure; Poverty indicators; Poverty threshold